Good to Bad or Bad to Bad? What is the relationship between valence and the trait content of the Big Two?. (28th August 2019) - Oliveira, Manuel; Garcia‐Marques, Teresa; Garcia‐Marques, Leonel; Dotsch, Ron
Abstract: In this article we directly assessed the relationship between valence and relevant traits of the Big Two dimensions (i.e., communion and agency). Drawing on previous research, we expected that the relationship with valence would be less monotonous and more variable in direction across agency‐related traits, compared to communion‐related traits. In three repeated measures studies we assessed the perceived valence of each trait dimension on a continuum of seven points. Studies 1 and 2 defined each continuum verbally. In Study 3 each continuum was defined by facial features. Results across these studies show that valence is linearly and more consistently related with communion‐related traits than with agency‐related traits. Within agency, however, competence established a positive linear relationship with valence, whereas dominance showed a target‐sensitive relationship with valence: quadratic in evaluation of trait concepts, and negative and linear in face evaluation. We discuss the implications of these data for Big Two‐related research.